Pengaruh Kualitas Layanan terhadap Kepuasan Konsumen pada Layanan Drive Thru McDonald’s Slamet Riyadi Surakarta - Sudarwati; Andre Louhena Nabayev; Supawi Pawenang (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The purpose of this research study examines the effect of service quality on customer satisfaction on the McDonald Slamet Riyadi Surakarta drive thru service. The research instruments used in this study were questionnaires, in this study there were 126 respondents of McDonald’s Slamet Riyadi Surakarta. The sampling technique used was purposive sampling. The criteria needed are consumers who use drive thru services. The data analysis method used in this test is the Partial Least Square (PLS) method. Data analysis includes testing the validity and reliability of the instrument, and testing the hypothesis statistically. Based on the results of analytical analysis using descriptive analysis methods and PLS, it can be concluded that service quality towards consumer satisfaction on McDonald's McDonald's Slamet Riyadi drive thru service is only a tangible variable which has the greatest contribution to customer satisfaction among 5 variables.